IMPLEMENTATION OF THE ROTATING TRIO EXCHANGE (RTE) MODEL IN LEARNING THE CONCEPT OF MOLECULAR GEOMETRY - Ismatul Ilmi; Ade Ismayani; Ratu Fazlia Indah Rahmayani (FKIP USK, 2020)
This study aims to describe the activities and responses of students to the RTE learning model on the concept of molecular geometry and to analyze the completeness of student learning outcomes. This is a descriptive study with a qualitative approach. The sample used in this study was class X MIA-2 MAN 6 Aceh Besar for the 2019/2020 school year. Data were collected by observing student activities, learning outcomes tests and questionnaire responses. The results of observing student activities for three meetings 1,2 and 3 respectively were 86%, 89.25% and 95%. The learning outcomes of students in class X MIA-2 MAN 6 Aceh Besar with the application of the RTE learning model on the molecular form material can be categorized as good, with the percentage of students who complete the completeness of 79.2%. 99.3% of students responded positively to the application of the RTE model.